2019
DOI: 10.1111/manc.12291
|View full text |Cite
|
Sign up to set email alerts
|

Public Debt Consolidation and its Distributional Effects

Abstract: We build a dynamic general equilibrium model with heterogeneous households, namely Rich and Poor, and capitalskill complementarity structure in the production function, to study aggregate and distributional implications of fiscal consolidation policies when the government uses a rich set of spending and tax instruments. Fiscal policy is conducted through constrained optimized fiscal rules. Our results show that, in the long run, fiscal consolidation enhances both aggregate efficiency and equity; however, it ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
(97 reference statements)
2
3
0
Order By: Relevance
“…Specifically, model 1 shows that a unit increase in the general government debt is associated with about 0.13% point increase in income inequality in SSA in the short run. This is not surprising in Africa because the results of the study corroborate the findings of some empirical studies such as Tung (2020), Sakkas and Varthalitis (2019), Arslan (2019), Azzimonti et al. (2014), and Salti (2015) who all found a positive and significant relationship between debt and inequality.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Specifically, model 1 shows that a unit increase in the general government debt is associated with about 0.13% point increase in income inequality in SSA in the short run. This is not surprising in Africa because the results of the study corroborate the findings of some empirical studies such as Tung (2020), Sakkas and Varthalitis (2019), Arslan (2019), Azzimonti et al. (2014), and Salti (2015) who all found a positive and significant relationship between debt and inequality.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 87%
“…Specifically, model 1 shows that a unit increase in the general government debt is associated with about 0.13% point increase in income inequality in SSA in the short run. This is not surprising in Africa because the results of the study corroborate the findings of some empirical studies such as Tung (2020), Sakkas and Varthalitis (2019), Arslan (2019), Azzimonti et al (2014), andSalti (2015) who all found a positive and significant relationship between debt and inequality. Also, the finding confirms the dynamic politico-economic theory Tax burden has a coefficient of 0.0045 and is statistically significant at 5%, suggesting that each percentage increase in tax burden increases inequality by about 0.45% point.…”
Section: Does Debt Increase or Decrease Inequality?supporting
confidence: 88%
See 1 more Smart Citation
“…These studies are summarized in Table 1. Sakkas and Varthalitis (2019) and Tung (2020) ascertain that public debt harms inequality for countries in the Euro Area and Asia-pacific region respectively. These studies taken together suggest that governments may use public debt as a means of reducing inequality.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Significantly lower domestic financing costs stemming from fiscal consolidation are associated with stronger growth dividends (Gupta et al, 2005). Income distribution may also improve or recover in the long run as stronger growth following a successful consolidation can improve the wage share or reverse its decline and reduce interest rates, which reduces capital income for richer households (IMF, 2014c;and Sakkas and Varthalitis, 2019).…”
Section: International Monetary Fund 14mentioning
confidence: 99%